2020
DOI: 10.3390/diagnostics10070468
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Biochemical Markers as Possible Indicators of Left Ventricular Abnormal Geometric Pattern and Function Impairment in Obese Normotensive Children

Abstract: Εmerging data indicate that various effects of obesity on the cardiovascular system can be evident during childhood. The aim of this study was to detect early changes in left ventricular structure and function in obese normotensive children and explore possible associations of these changes with anthropometric and biochemical parameters. Normotensive 8–11-year-old obese and normal weight children were included in the study. They all underwent anthropometric measurements, laboratory tests, and echocardiography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Both obese children and CKD patients are at risk of developing LVH, which is confirmed by data from clinical trials. In obese children without hypertension, LVH was found in 47.2% and correlated with WHtR ( 17 ). In a large group of children from the Chronic Kidney Disease in Children study, higher BMI also significantly increased the risk of LVH ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both obese children and CKD patients are at risk of developing LVH, which is confirmed by data from clinical trials. In obese children without hypertension, LVH was found in 47.2% and correlated with WHtR ( 17 ). In a large group of children from the Chronic Kidney Disease in Children study, higher BMI also significantly increased the risk of LVH ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, obesity was also associated with LVG remodeling, and the magnitude of the association of obesity with CH was the strongest, followed by EH and CR. A study including 62 normotensive children aged 8-11 years showed that elevated WHtR increased the odds of any phenotype of LVG remodeling ( 8 ). A study among 526 children aged 6-15 years found that neither obesity (defined by BMI) nor WC Z-score was associated with CR, whereas obesity and WC Z-score was independently associated with EH and CH ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, participants converting from CR to normal geometry had decreased risk of all-cause mortality (16). LVH has been the most common target organ damage in children and adolescents with hypertension (17), and obesity is strongly associated with abnormal LVG modeling (8)(9)(10)(11). Therefore, assessing the presence of LVH and LVG in the early life using a simple and effective obesity-related indicator could be helpful to prevent target organ damage such as LVG remodeling in the short term and the CVD outcomes in the long term.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is related to cardiovascular (CV) risk (including hyperglycemia, elevated blood pressure, dyslipidemia, metabolic syndrome, and insulin resistance) (5) and short-term target organ damage (6, 7) in childhood. For example, obesity increases the risk of left ventricular hypertrophy (LVH) and left ventricular geometric (LVG) remodeling (8)(9)(10)(11) (markers of cardiac structural damage), which are independent predictors of cardiovascular disease (CVD) (12,13).…”
Section: Introductionmentioning
confidence: 99%